2005
DOI: 10.1002/syn.20191
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the plant-derived κ-opioid hallucinogen salvinorin A in nonhuman primates

Abstract: Salvinorin A, a potent hallucinogen isolated from the leaves of Salvia divinorum, has gained popularity among adolescents in the USA. No detailed study of the pharmacokinetics has been conducted in vivo. The present study investigates the in vivo pharmacokinetics of salvinorin A (0.032 mg/kg, i.v. bolus) in rhesus monkeys (n=4, 2 male, 2 female). The elimination t(1/2) was rapid (56.6+/-24.8 min) for all subjects. Pharmacokinetic differences (distribution t(1/2), elimination t(1/2), and AUC) were observed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 18 publications
(22 reference statements)
5
91
0
1
Order By: Relevance
“…than the s.c. route in males. Reasons for this are unclear but may be related to pharmacokinetic factors, possibly limiting bioavailability by the s.c. route (Schmidt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…than the s.c. route in males. Reasons for this are unclear but may be related to pharmacokinetic factors, possibly limiting bioavailability by the s.c. route (Schmidt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…in male and female rhesus monkeys (Schmidt et al, 2005a). Although the overall elimination t 1/2 was 56.6 Ϯ 24.8 min, distinct gender differences were observed: in male monkeys, there was a rapid t 1/2 for distribution, elimination t 1/2 was 37.9 Ϯ 5.6 min, and the area under the dose-response curve was 572 Ϯ 133 ng ⅐ min Ϫ1 ⅐ ml Ϫ1 , whereas in female monkeys, t 1/2 for distribution was slower (0.95 Ϯ 0.2 min), the t 1/2 for elimination was 80.0 Ϯ 13.1 min, and the area under the dose-response curve was 1087 Ϯ 46 ng ⅐ min Ϫ1 ⅐ ml Ϫ1 .…”
Section: B Pharmacokinetic Properties Of Salvinorin Amentioning
confidence: 99%
“…It was also demonstrated ex vivo that salvinorin B is the major metabolite of salvinorin A in nonhuman primates . The concentration of salvinorin B was below the limit of quantitation in rhesus monkey plasma, however, suggesting that this metabolite is either cleared rapidly or accumulates in organs or tissues (Schmidt et al, 2005a). That salvinorin A is rapidly metabolized is supported by the finding that only approximately 0.8% of an administrated dose of salvinorin A (0.5 mg) was extracted from urine in human volunteers (Pichini et al, 2005).…”
Section: A Metabolism Of Salvinorin Amentioning
confidence: 99%
“…Intravenous administration of Sal A increased prolactin levels in rhesus monkeys, but the duration was only 30 min, shorter than that of U69,593 (90 min) at the same dose (Butelman et al, 2007). A pharmacokinetic study in nonhuman primates showed that the elimination t 1/2 of Sal A in the serum was less than 1 h (Schmidt et al, 2005a).…”
mentioning
confidence: 94%
“…However, Sal B was not detected in the blood after i.v. injection of Sal A in rhesus monkeys (Schmidt et al, 2005a). Sal B may be accumulated in the extravascular compartment or be excreted via other routes.…”
mentioning
confidence: 99%